2011
DOI: 10.1111/j.1755-0238.2011.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoke application to field-grown Merlot grapevines at key phenological growth stages on wine sensory and chemical properties

Abstract: Background and Aims: Smoke exposure of grapevines and development of smoke taint in wine are issues of increasing incidence and severity. There is limited understanding of the effect of phenological stage at the time of smoke exposure on taint development. The aim of this study was to demonstrate the variation in smoke uptake and taint development between and within seasons. Methods and Results:Smoke was applied to field-grown Merlot grapevines at 12 stages of vine development over three growing seasons. Key p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 32 publications
1
89
0
Order By: Relevance
“…2009, Hayasaka et al. 2010a,b,c) and the influence of grapevine phenology on the extent of smoke taint in wine (Kennison et al. 2009, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2009, Hayasaka et al. 2010a,b,c) and the influence of grapevine phenology on the extent of smoke taint in wine (Kennison et al. 2009, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A peak of sensitivity occurring from 7 days post-veraison was confirmed. As for seasonal effects, no carryover of guaiacol or 4-methyl guaiacol was seen between seasons; however, yield appears to have been reduced within season by~24% and in the season following exposure bá»č 50% (Kennison et al 2011). Further research will determine if these effects on yield are reproducible.…”
Section: Research To Datementioning
confidence: 94%
“…Guaiacol was the predominant volatile phenol ranging from 0 to 100 mg/L for single treatments or a total of~400 mg/L for repeated exposure. In a recent report (Kennison et al 2011), smoke applied at 12 stages of development over three seasons revealed key periods of vine sensitivity to smoke taint in the wine. Thus, 'low' and 'variable' levels of taint were evident where exposure occurred from 'shoots at 10 cm to full bloom' and from 'pea size berries to onset of veraison', respectively.…”
Section: Research To Datementioning
confidence: 97%
See 1 more Smart Citation
“…In an extension to this study, smoke was applied to field‐grown Merlot grapevines at 12 stages of vine development over three growing seasons (Kennison et al. ). Differences in a vine's sensitivity to smoke taint in wine were observed among the different growth stages.…”
Section: Smoke Exposure Of Grapes and Vines Berry Composition And Wmentioning
confidence: 99%